ANALISIS KARAKTERISTIK PENGGUNAAN MEDIA SOSIAL PADA DINAS KOMUNIKASI DAN INFORMATIKA KOTA MAKASSAR - Yusmanizar Ibrahim Hernald; Thahir Haning; Alimuddin Unde; Muhammad Yunus (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
The very rapid development of the use of social media has touched the government sector. It is hoped that the use of social media can connect public officials and the community to be able to support the implementation of better governance. This research was conducted to analyze the characteristics of social media. The results of this study indicate that the characteristics of social media in Makassar City are based on an analysis of the Kominfo social media accounts, it is found that the content data on the Kominfo social media is homogeneous. There are three types of Social Media for the Makassar City Communication and Information Service, namely Facebook with the account name of the Makassar City KOMINFO Service, Twitter with the DISKOMINFO MAKASSAR account name, and the type of social media Instagram with three account names, namely lalinmks, callcentre112mks and Diskominfomks.